Always a catch!: how I punched my way into marrying a prince, 4 - Momoyo, Mayo; Mito, Itsuki (Always a catch!, 2025)
In the Kingdom of Rubini, the royal castle is set to host an evening party where Maria is to be officially announced as Prince Renato's fiancée. In anticipation of the event, she must make sure she's all brushed up on proper dancing and manners! But will the culprit behind the attack on Maria and the queen be unmasked before the party?Something serious is definitely on the horizon! Will our two lovebirds be able to overcome disaster?!